‘Time's relentless melt’: The severity of life imprisonment through the prism of old age - Vannier, Marion (Punishment & society, 2023)
This paper considers the pains of life-sentence imprisonment through the novel vantage point of old age understood as a process. Our prison populations are getting older and the use of life sentences is dramatically increasing. Yet, research, campaigning, law and policy have not addressed the long-term consequences of imposing life sentences on prisoners who will age. Whilst far from exhaustive, our study draws on studies in gerontology, health policy and penology. We rely on shared analysis of collected official data from the US and the UK to highlight how the expansion and growth of life sentences on the one hand, and the dramatic aging of the prison population, on the other, are intertwined and need to be considered together. This article emphasizes the urgency of taking a holistic approach to penal severity, one that includes analyses of scale, lived experiences, as well as of law and politics, to uncover the multiple forms of marginalization elderly prisoners are exposed to. Aging is a phenomenon we will all experience, yet, in the context of imprisonment, we argue that old age is a ‘prison problem’ rather than a ‘prisoner problem,’, urging research and policy to depart from the conventional and reductive view of the older prisoner as one in need of transformation and treatment or as being inherently criminal.